Pulsed current-mode signaling for nearly speed-of-light intrachip communication. - Jose, A.P (IEEE Journal of solid state circuits)
In this paper, we describe the design of on-chip repeater-less interconnects with nearly speed-of-light latency. Sharp current-pulse data transmission is used to modulate transmitter energy to higher frequencies, where the effect of wire inductance is maximized, allowing the on-chip wires to function as transmission lines with considerably reduced dispersion. A prototype 8-Gb/s serial link employing this pulsed current-mode signaling in a 0.18-μm CMOS process is described and measured.